Targeting Protein Neddylation to Inactivate Cullin-RING Ligases by Gossypol: A Lucky Hit or a New Start? - Yu Q; Sun Y (Dove Medical Press, 2021)
Qing Yu,1– 3 Yi Sun3 1Department of Head and Neck Surgery, The Cancer Hospital of the University of Chinese Academy of Sciences (Zhejiang Cancer Hospital), Institute of Basic Medicine and Cancer (IBMC), Chinese Academy of Science, Hangzhou, Zhejiang, People’s Republic of China; 2Key Laboratory of Head & Neck Cancer Translational Research of Zhejiang Province, Hangzhou, Zhejiang, People’s Republic of China; 3Cancer Institute of the Second Affiliated Hospital and Institute of Translational Medicine, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Yi SunCancer Institute of the Second Affiliated Hospital and Institute of Translational Medicine, Zhejiang University School of Medicine, 268 Kaixuan Road, Hagnzhou, Zheijiang, People’s Republic of ChinaTel +86 571 86971812Fax +86 571 88981576Email yisun@zju.edu.cnAbstract: Cullin-RING E3 ligases (CRLs) are the largest family of E3 ubiquitin ligases, responsible for about 20% of the protein degradation by the ubiquitin-proteasome system (UPS). Given their vital roles in multiple cellular processes, and over-activation in many human cancers, CRLs are validated as promising targets for anti-cancer therapies. Activation of CRLs requires cullin neddylation, a process catalysed by three neddylation enzymes. Recently, our group established an AlphaScreen-based in vitro cullin neddylation assay and employed it for high-throughput screening to search for small-molecule inhibitors targeting cullin neddylation. During our pilot screen, gossypol, a natural product extracted from cottonseeds, was identified as one of the most potent neddylation inhibitors of cullin-1 and cullin-5. We further demonstrated that gossypol blocks cullin neddylation by binding to cullin-1/-5 to inactivate CRL1/5 ligase activity, leading to accumulation of MCL-1 and NOXA, the substrates of CRL1 and CRL5, respectively. The combination of gossypol and an MCL-1 inhibitor synergistically enhanced the anti-proliferative effect in multiple human cancer cell lines. Our study unveiled a rational combination of two previously known inhibitors of the Bcl-2 family for enhanced anti-cancer efficacy and identified a novel activity of gossypol as an inhibitor of CRL1 and CRL5 E3s, thus providing a new possibility in the development of novel CRL inhibitors for anti-cancer therapy.Keywords: anti-cancer drug, cullin-RING E3 ligases, natural product, high-throughput screen, neddylation, small-molecule inhibitors